A representação do trabalho feminino em Os Corumbas, de Amando Fontes, e Em Surdinas, de Lúcia Miguel Pereira: um olhar sob a ótica do dano existencial - Massola, Ivone (My University, 2019)
The theme of this thesis is the study of existential damage regarding its weighting from the process of fictional reading. The fictional texts of the novels of 30 in Brazil allow various possibilities of analysis, because of the social nature of their narratives. In corpora Os Corumbas and Em surdina, the female characters suffer existential damage due to a common theme, work. In the first one, the proletarians of the textile industries in Sergipe in the 1920s suffer existential damage, since work is the only means of subsistence, but it is in this environment of public exposure that they fall into prostitution. In Rio de Janeiro, during the same period, Cecília is a woman from bourgeois origin who is prevented from occupying a job because of prejudice, since her father fears family disgrace if she has access to a job. Existential damage is characterized when an individual loses his/her life projects or his/her life of relationship, because of third parties, that prevent the free exercise of his/her existence as a person. The interdisciplinarity connecting the study of language and literature (area of study which is called Letras in Brazilian Portuguese) and Law materializes through the hermeneutic interpretation of the aesthetic effect literary theory, developed by German Wolfgang Iser, and Jurisprudentialism, theorized by the Portuguese philosopher António Castanheira Neves, trying to find the possible convergences in the theories that the reading of the texts has in commom regarding the two areas. The analysis of the characterization of the existential damage starts from Italian doctrine, where the legal institute of existential damage was born, with deeper investigations conducted by Paolo Cendon and Patrizia Ziviz. Starting from fiction, it is possible to begin by the reading of concrete legal cases, which made history in the contemporary legal universe, since one deals with the first case of existential damage judged in the state of Rio Grande do Sul and the other addresses the case of a young maid, who was kept under slave labor in Bahia.
O tema da presente tese é o estudo do dano existencial frente a sua ponderação a partir do processo de leitura ficcional. Os textos ficcionais dos romances de 30 no Brasil se prestam a diversas possibilidades de análise, graças ao cunho social das suas narrativas. Nos corpora Os Corumbas e Em surdina, as personagens femininas sofrem dano existencial perante um tema comum, o trabalho. No primeiro, as proletárias das indústrias têxteis sergipanas nos anos 20, sofrem dano existencial, pois o trabalho é o único meio de subsistência, mas é nesse ambiente de exposição pública que elas caem na prostituição. Já no Rio de Janeiro, no mesmo período, está Cecília, mulher de origem burguesa impedida de ocupar um posto de trabalho por preconceito, já que o pai teme o desprestígio familiar se ela tiver acesso a um posto de trabalho. O dano existencial se caracteriza quando um indivíduo perde seus projetos de vida ou a sua vida de relação, por culpa de terceiros, que impedem o livre exercício da sua existência enquanto pessoa. A interdisciplinaridade unindo Letras e Direito se materializa com a interpretação hermenêutica da teoria literária do efeito estético, do alemão Wolfgang Iser, e do Jurisprudencialismo, teorizado pelo filósofo do Direito português António Castanheira Neves, busca-se encontrar as convergências possíveis nas teorias que a leitura dos textos têm em comum entre as duas áreas. A análise da caracterização do dano existencial parte da doutrina italiana, nascedouro do instituto jurídico de dano existencial, com pesquisas mais profundas de Paolo Cendon e Patrizia Ziviz. Partindo-se da ficção, chega-se à leitura e análise de casos jurídicos concretos, os quais fizeram história no universo jurídico contemporâneo, pois um trata do primeiro caso de dano existencial julgado no estado do Rio Grande do Sul e o outro aborda o caso da jovem empregada doméstica, mantida sob trabalho análogo à condição de escrava, na Bahia.
Keywords: Existencialismo na literatura; Jurisprudência; Mulheres - Emprego; Existentialism in literature; Jurisprudence; Women Employment